2022
DOI: 10.1155/2022/6831167
|View full text |Cite
|
Sign up to set email alerts
|

Bus Single-Trip Time Prediction Based on Ensemble Learning

Abstract: The prediction of bus single-trip time is essential for passenger travel decision-making and bus scheduling. Since many factors could influence bus operations, the accurate prediction of the bus single-trip time faces a great challenge. Moreover, bus single-trip time has obvious nonlinear and seasonal characteristics. Hence, in order to improve the accuracy of bus single-trip time prediction, five prediction algorithms including LSTM (Long Short-term Memory), LR (Linear Regression), KNN (K-Nearest Neighbor), X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…These results deviate from those of previous studies that indicated better predictive capabilities of LSTM than the RF on time-series data [ 31 ]. However, these results agree with the findings of other investigations that reported comparable predictive performance between these two ML models [ 32 , 33 ]. We postulate that one contributing factor to this inconsistency may be the limited sample size and relatively uncomplicated model structure employed in this study [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results deviate from those of previous studies that indicated better predictive capabilities of LSTM than the RF on time-series data [ 31 ]. However, these results agree with the findings of other investigations that reported comparable predictive performance between these two ML models [ 32 , 33 ]. We postulate that one contributing factor to this inconsistency may be the limited sample size and relatively uncomplicated model structure employed in this study [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Unlike the GBDT, the complexity of the model is controlled by using a regular function, so it is an "upgraded" version of the GBDT model. The objective function of the model is shown in Equation (6).…”
Section: Gbdt Model and Xgboost Modelmentioning
confidence: 99%
“…Sun et al [5] used the data of Xi'an Metro Line 2 to prove that the prediction junction effect of XGBoost is better than that of the back propagation neural network model and ARMA model. Huang et al [6] used three integration methods, including Adaboost, to integrate five models: long short-term memory (LSTM), linear regression, K-nearest neighbor (KNN), XGBoost and gate recursive unit (GRU), and then predicted the single bus trip time. Xu et al [7] realized short-term passenger flow prediction by establishing the GBDT model and proved that the model was superior to the linear model and back propagation neural network.…”
Section: Introductionmentioning
confidence: 99%